GE_GERICHTE C/9292/2015 vom 18. April 2018 - GE Cour de justice (2018)
SALAIRE ; RÉSILIATION IMMÉDIATE ; INDEMNITÉ JOURNALIÈRE ; AVANCE(EN GÉNÉRAL) ; DOMMAGE | CO.337.al1; CO.322.lete.ch1; CO.337.letc; .321.lete.ch1